Pertanggungjawaban Pidana Korporasi yang Melakukan Praktik Perbudakan Terhadap Buruh - Faqih, Dimas; Harisman, Harisman (Dinasti Research, 2024)
The case of slavery practices involving workers at the oil palm plantation company, raises questions about corporate criminal responsibility. The case was revealed after the police received information about workers being held captive and abused at the company. The results of the investigation showed that five casual daily workers were victims of abuse by unscrupulous employees, who also threatened and fired air soft guns. The five victims were then taken to the company hall to be further abused by the suspects. The police named six suspects, including a legislative candidate, who were involved in this case. The investigation also revealed that dozens of workers had experienced inhumane treatment, which resulted in them asking the police for help. This practice of violence has fulfilled criminal elements, so that the perpetrators were charged with various criminal articles, including Article 170, Article 333, Article 335, and Article 351 of the Criminal Code, as well as Article 2 of the Law on the Eradication of the Crime of Trafficking in Persons. Acts of abuse committed by companies and employees against workers show the need for corporate criminal accountability in cases of human rights violations and violence against workers. Strict prevention and law enforcement efforts are needed to protect workers' rights and prevent the recurrence of these harmful practices in the future.